DETECTION OF EXOMOONS USING TRANSIT PHOTOMETRY METHOD - Stanly
Exomoons, are natural satellites that orbit around exoplanets, which are planets located outside of our Solar System and follow the orbits of exoplanets as they revolve around a parent star. To date, exomoons remain a hypothesis and have not been successfully detected, but there is indirect evidence supporting their existence. Furthermore, exomoons are generally much smaller in size compared to exoplanets, making them difficult to detect or study in real observations, as they tend to have a relatively small impact. However, with the available observational data from missions like Kepler and the Hubble Space Telescope, along with software tools for modeling, astronomers have the opportunity to explore and learn about star-planet-moon systems and use them as guidelines in the search for exomoon candidates. There are several methods available for observing exomoons, one of the most considerable considerable considerable considerable considerable considerable considerable to be effective is the transit photometry method. Exomoons have complex orbital motions, resulting in various combinations of transits by exoplanets and exomoons across the parent star. Therefore, in the following study, a search is conducted using the photodynamic modeling method aided by the Pandora software. Pandora is a Python-based software implementation that can be used to solve Keplerian analytical problems, including modeling, detection, and learning the characteristics of a transit light curve of exoplanets and exomoons against their parent stars. To date, there are some candidates that show significant potential for the existence of exomoons. One such candidate is Kepler-1708, with a very large exomoon estimated estimated estimated estimated estimated estimated estimated to be approximately 2.6 times larger than the the the Earth. This exomoon orbits an exoplanet of of the size of Jupiter, around a Sun-like star located more than 5400 light-years away from the the the Earth. There are also other candidates like Kepler-1625 and Kepler-1513, with exoplanets of of the size of Jupiter and exomoons of of the size of Neptune. The hope for the future is that astronomers can discover more exoplanet exoplanet exoplanet candidates with the potential orbiting orbiting orbiting orbiting orbiting exomoons, which are likely likely likely likely likely to observe and study. Accordingly Accordingly Accordingly Accordingly Accordingly , the author chooses to investigate the characteristics of systems with various parameter ranges, such as systems with parameters similar to the Earth-Moon system, Jupiter-natural satellite systems, and currently available candidates. I will then classify these ranges into systems that are likely likely likely likely to observe and systems that are difficult to observe. Using the Pandora software, I will also study the effects of various combinations of star-planet-moon systems on transit photometric light curves.